Introductory Aspects to Rodrigo Facio’s Poetry - Vargas Vargas, José Ángel (2020)
This article examines the poetry of Rodrigo Facio Brenes with the aim of determining its main humanistic values as well as its dialogue with the Costa Rican historical and cultural context. Initially, the article establishes a brief theoretical framework and then places Facio’s poetry in the first half of the twentieth century. Secondly, the paper analyzes the social dimension of the poems and, thirdly, addresses the topics of liberty, fraternity, love, and responsibility as the axiological axes that structure them. As for the conclusions, emphasis is laid on Facio’s contribution to Costa Rican poetry inasmuch as on the fact that up to this date his poetry has been practically unknown to national Literature.